STRATEGI PEMASARAN DALAM MENINGKATKA PELAYANAN PERBANKAN SYARIAH - Ayu, Zaula Putri; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
Marketing strategy is the right first step to face increasingly fierce competition in promoting a product in the era of globalization. Some analysis can be done to determine the marketing strategy used by a company.  Marketing strategy is the company's goal, such as improving Islamic banking services. This research adopts a descriptive method with a qualitative approach. The 4P theory (product, price, place, promotion) is also applied in this study with an analysis that provides banking services that are easy to use, safe, and provide a positive experience for customers in transactions. The focus of the research is to understand the marketing strategy and analyze its impact on interest in saving and transactions.